Insulin-Like Growth Factor-1 Is Neuroprotective in Aged Rats With Ischemic Stroke - Serhan, Ahmad; Boddeke, Erik; Kooijman, Ron (Frontiers in Aging Neuroscience, 2019)
Post-stroke systemic injections of insulin-like growth factor-1 (IGF-1) exert neuroprotective effects in rats. In the current study, we aimed to test the efficacy of IGF-1 neuroprotection in aged rats (24–25 months old) and to compare the results with adult rats (6–7 months old). Furthermore, we addressed putative differences in microglial responses to IGF-1 in adult and aged rats. Rats were subjected to ischemic stroke while they were conscious by infusing endothelin-1 (Et-1) through a guide cannula that was implemented in the vicinity of the middle cerebral artery (MCA). Rats were given subcutaneous injections of IGF-1 (1 mg/kg) at 30 min and 120 min after the insult. Post-stroke IGF-1 treatment reduced the infarct size by 34% and 38% in aged and adult rats, respectively. The IGF-1 treated adult rats also showed significant improvement in sensorimotor function following stroke, while this function was not significantly affected in aged rats. Furthermore, aged rats displayed exaggerated activation of microglia in the ischemic hemisphere. Significant reduction of microglial activation by IGF-1 was only detected at specific regions in the ipsilateral hemisphere of adult rats. We show that IGF-1 reduced infarct size in aged rats with an ischemic stroke. It remains to be established, however, whether the age-related changes in microglial function affect the improvement in behavioral outcomes.